The act of giving: a pilot and feasibility study of the My Life Story programme designed to foster positive mental health and well-being in adolescents and older adults. Issue 2 (3rd April 2017) - Knight, Tess; Skouteris, Helen; Townsend, Mardie; Hooley, Merrilyn
Abstract : Twelve pairs of adolescent students were linked to an older adult in aged care in this pilot study on intergenerational interaction. Triads met weekly for eight weeks with the aim of writing a Life Review Book for the older adult. At the conclusion of the study, participants were interviewed to gain an understanding of their experiences and meaning of the programme. Thematic analysis of the interviews revealed four major themes: breaking down the stereotypes, recognition of heterogeneity, satisfaction from 'making the effort' and personal gain through making a contribution. Measures of psychological well-being were also administered pre- and post-delivery of the programme. This revealed that both age groups could and would complete all aspects of the programme. It was concluded from the findings that the intergenerational programme is feasible in the context of adolescent and older adult intergenerational relationships, and a potential influence on well-being for those who take part.